A Literature Review of Health Economic Evaluation: A Case of Vaccination on systematic review analysis - Trung Quang Vo, Arthorn Riewpaiboon (Journal of Applied Pharmaceutical Science, 2016)
Background: This study tries to provide a comparative analysis of the systematic review of economic evaluation literature available about vaccines. Methods: PubMed database were searched by using the following keywords: “vaccination/economics [MeSH]”. All articles were included if: 1) A literature or systematic review of vaccination studies; 2) primary or secondary data; 3) published in English; 4) related to human. Exclusion criteria were as followings: 1) editorial, review or methodological articles; 2) not in health sector; 3) not applied from 2009 to 2013.Results: From 22 records found, eleven articles met selection criteria. Only 27.3 percent (3 of 11 studies) was recorded about the methodology of conducting systematic review studies based on the PRISMA, and AMSTAR guideline. Two of eleven studies (18.1 percent) in this review, the authors evaluated the quality of vaccination systematic review studies with different levels including “Moderate” to “Moderate to good” and “Moderate to good”.Discussion and conclusion: According to this study, it helps to understand the current situation for conducting and reporting the economic evaluation of vaccination systematic review studies. Currently, the large number of studies and systematic reviews on the effects of vaccination, high quality evidence to inform policy decisions on how best to use vaccination in health care is still lacking.
Keywords: Economic analysis, economic evaluation, vaccination, systematic review, literature review.